Why mental health service delivery needs to align alongside mainstream medical services - Javed Latoo (14777125) (2022)
There is significant individual human suffering and economic burden because of untreated mental health and substance use disorders. There is high psychiatric morbidity in primary and secondary medical care. At least one-fifth of patients attending primary care services in western countries pertain to mental health and one-third of patients attending general hospitals have a comorbid mental disorder. Patients with mental disorders have lower life expectancy than the general population due to various medical conditions and reduced access to physical healthcare. There is a suicide every 40 seconds and the vast majority of those who die by suicide have a diagnosable mental disorder. Despite this, most countries spend less than 2% of their health budgets on mental health. Effective treatments exist for mental disorders, however underfunding, poor integration of services, lack of trained health care professionals and stigma often prevent access to effective treatments. Stigma is a significant barrier to seeking help and receiving treatment. Geographical separation of mental health services from general hospital settings may be perpetuating the stigma of mental illness among the population. In this article, we review the key reasons why mental health services globally need to align with mainstream healthcare services and the longstanding reasons that necessitate the need to make mental health a public health priority. Other Information Published in: Asian Journal of Psychiatry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ajp.2022.103053